PENGARUH PERENCANAAN PAJAK DAN BEBAN PAJAK TANGGUHAN TERHADAP MANAJEMEN LABA (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015-2017) - indra saputra; rusmanto -; Aulia Ariska (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2020)
The purpose of this study is to determine the effect of tax planning and deferred tax expense to earnings management that has not been proven empirically on manufacturing companies listed on the Indonesia Stock Exchange in 2015-2017. The sample drawn by purposive sampling and fulfill sample selection criteria. Method of data analysis using logistic regression. The results of this study indicate that the variable tax planning and deferred tax burden simultaneously have a significance value of 0.087 for Profit Management. Partially, tax planning has a significance of 0.043 and deferred tax expense has a significance of 0.675 to Profit Managemen.